Analisis Citra Kuning Telur Berbasis Ekstraksi Ciri Statistika Orde Satu untuk Mengenali Jenis Telur Ayam Ras dan Ayam Kampung - Sipan, Muhammad; Pramuyanti, Rony Kartika (Elektrika, 2021)
Chicken eggs are one of the most familiar side dishes in Indonesia besides tempeh. High protein and low prices make eggs a favorite side dish for the people of Indonesia. Although almost every day we see egg yolks we often can't tell for sure what chicken egg yolks we see. Based on this, the author tries to study egg yolk imagery based on first-order feature extraction using various features such as variance, skewness, carding, entropy, and mean. Statistical calculations are used based on the pixel values of the original image in this first-order texture calculation with the sole purpose of finding the histogram properties of the image. The results of first-order statistical characteristic calculations were used to differentiate between native and purebred chicken eggs. This study facilitates decision making, especially in the selection of accurate and measurable egg yolks from several types of chicken eggs, thereby minimizing public mistakes in choosing eggs based on egg yolks. The first step that can be done is to determine the data consisting of various types of images of free-range chicken egg yolks. These are free-range chicken eggs and purebred chicken eggs. The image is then segmented by separating the yolk and white, then first-order statistical analysis which later the results of these statistical calculations can be used as a reference in determining the type of egg. The results of the trial resulted in first-order feature extraction statistical values, namely for native chickens, the mean value was 132.743, min 69.5255, max 252.5, standard deviation was 29.922 and variance was 905.882. The average value of statistics was order 1 for native chickens. of mean 137,176, min 48, max 240.2, standard deviation 31,454 and variance of 957.89.